Romans : a handbook on the Greek text - Porter, Stanley E.; Yoon, David I. (Waco : : Baylor University Press, 2023)
"A linguistic and grammatical analysis of the Greek text of the Epistle to the Romans"-- Provided by publisher.
Keywords: Bible. Romans -- Criticism, Textual